Strategi Komunikasi Pemasaran PT Grahawita Santika dalam Memasarkan Hotel Amaris Jakarta - Yosafat Basal Susilo (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The purpose of this study is to determine PT Grahawita Santika’s point of view about marketing communication, the mixs in marketing management doing by PT. Grahawita Santika in marketing Amaris Panglima Polim Jakarta and the reasons of choosing traveler as the targets. The method used in this research is qualitative with case study design. The theory used is symbolic interaction, social construction and Theory of Gaps Model. The datas collected through observations, interviews and document analysis. The results showed that: (1) PT Grahawita Santika markets Amaris Panglima Polim Jakarta as a smart hotel with the concepts of smart location, smart employee and smart services. (2) Mixs of marketing communication used in marketing the Amarishotel is by advertisement, personal selling, sales promotion, public relations and publications, (3) The selection of Business Traveler and Leisure Traveler as the target caused by PT Grahawita Santika saw the potential which might be met by the hotel Amaris PanglimaPolim Jakarta.